Strategic positioning and accelerating regulatory clearance for new ventures - Pahnke, Emily Cox; Žužul, Tiona; Howard, Michael D. (Strategic Management Journal, 2026)
Abstract Research Summary How do new ventures strategically position their products to accelerate regulatory clearance? We investigate this question in the medical device industry, where regulatory clearance is a prerequisite for market entry. We examine 239 new firms' 510(k) device clearances by the FDA between 2001 and 2019. Our approach combines quantitative analysis of firms' claims of similarity with extensive field research. We find that strategic positioning significantly impacts time to clearance, and that effective strategies evolve over time. For first products, firms accelerate clearance by citing fewer reference products while strategically positioning relative to same‐category products and to category exemplars; for second products, firms accelerate clearance by referencing their own products. These findings extend positioning theory into regulatory contexts and reveal how a firm's optimal strategic positioning changes across successive products. Managerial Summary We study how new medical device startups can speed up regulatory approval by strategically positioning their products for the FDA. Analyzing 239 firms' 510(k) clearances from 2001 to 2019, we find that the way companies frame their products for regulators plays a key role in how quickly they are cleared. For their first products, firms benefit from referencing fewer existing devices and aligning with well‐known or similar products. For their second product, referencing their own previously cleared device helps accelerate the process. Our findings show that positioning is a powerful tool for navigating regulatory hurdles. We highlight how the most effective strategy changes as a company grows, offering practical guidance for leaders bringing new medical technologies to market.